Athletes with exercise-associated fatigue have abnormally short muscle DNA telomeres - Collins, M.; Renault, V.; Grobler, L. A.; St. Clair Gibson, A.; Lambert, M. I.; Wayne Derman, E.; Butler-Browne, G.; Noakes, T. D.; Mouly, V. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION/PURPOSE: Although the beneficial health effects of regular moderate exercise are well established, there is substantial evidence that the heavy training and racing carried out by endurance athletes can cause skeletal muscle damage. This damage is repaired by satellite cells that can undergo a finite number of cell divisions. In this study, we have compared a marker of skeletal muscle regeneration of athletes with exercise-associated chronic fatigue, a condition labeled the "fatigued athlete myopathic syndrome" (FAMS), with healthy asymptomatic age- and mileage-matched control endurance athletes. METHODS: Muscle biopsies of the vastus lateralis were obtained from 13 patients diagnosed with FAMS and from 13 healthy control subjects. DNA was extracted from the muscle samples and their telomeric restriction fragment (TRF) or telomere lengths were measured by Southern blot analysis. RESULTS: All 13 symptomatic athletes reported a progressive decline in athletic performance, decreased ability to tolerate high mileage training, and excessive muscular fatigue during exercise. The minimum value of TRF lengths (4.0 +/- 1.8 kb) measured on the DNA from vastus lateralis biopsies from these athletes were significantly shorter than those from 13 age- and mileage-matched control athletes (5.4 +/- 0.6 kb, P < 0.05). Three of the FAMS patients had extremely short telomeres (1.0 +/- 0.3 kb). The minimum TRF lengths of the remaining 10 symptomatic athletes (4.9 +/- 0.5 kb, P < 0.05) were also significantly shorter that those of the control athletes. CONCLUSION: These findings suggest that skeletal muscle from symptomatic athletes with FAMS show extensive regeneration which most probably results from more frequent bouts of satellite cell proliferation in response to recurrent training- and racing-induced muscle injury.